Impact of environmental conditions on the signal of 650 nm semiconductor lasers - Al-Karawi, Safana Saad Salih; Habeeb, Ammar Ayesh; Nazhan, Salam; Al-Karawi, Ahmed (Edelweiss Applied Science and Technology, 2024)
This study investigates the influence of various environmental factors, particularly temperature, relative humidity, smoke, and dust particles, on the optical output power (P) of a 650 nm semiconductor laser. The effects of environmental factors on beam transmission are experimentally investigated with embedded messages and without. The experiments are conducted with a laser under different environmental factors to simulate typical operating conditions for optical devices. The results show that the transmitted signal with the message gradually decreases in P from 317.5 µW to 255.2 µW with increasing temperature from 28 °C to 55 °C. When the relative humidity increases from 10% to 80%, the P decreases from 245.3 µW to 67.5 µW similar to the case of the temperature effect. However, with the massage scenario humidity less affected the laser signal. Furthermore, when measuring the P at a smoke concentration of 182 ppm to 268 ppm, its value decreases from 305.4 µW to 54.4 µW, which shows less effect than temperature and humidity. The dust density used in the channel is 8.57 mg/m³ to 208.44 mg/m³ to simulate different amounts of airborne particles found in various environments to study their effect on the signal. The power signal has decreased dramatically as the dust concentration increases, with and without massage. As observed from the results, smoke concentration has a minimal impact compared to other factors, temperature fluctuations, humidity, and dust density. These results give useful information for applications that used transmitting data under similar environmental conditions, making this work suitable for providing insights into different atmospheric conditions.